2009
DOI: 10.1115/1.3197141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Friction on Coupled Contact in a Twisted Wire Cable

Abstract: A strand or cable consists of a central core surrounded by a number of wires wound helically in a single layer or multilayers. There are three modes of contact in a simple straight strand. The first type is a core-wire contact in which the wires in the layer are in contact with the core only. In the second type, the wires in the layer are in contact among themselves and not with the core, while in the third type there is a coupled contact among the core and all the wires. Most literature handled the cable asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…(12) in the mentioned paper) results in an indeterminate form as the coefficient of friction tends to zero. Note also that since Gnanavel et al (2010) do not consider the effects of local contact deformations, their results cannot be applied in the frictionless case.…”
Section: Coupled Core-wire and Wire-wire Contactmentioning
confidence: 95%
See 1 more Smart Citation
“…(12) in the mentioned paper) results in an indeterminate form as the coefficient of friction tends to zero. Note also that since Gnanavel et al (2010) do not consider the effects of local contact deformations, their results cannot be applied in the frictionless case.…”
Section: Coupled Core-wire and Wire-wire Contactmentioning
confidence: 95%
“…The case of coupled contact between the core and all the wires was recently considered by Gnanavel et al (2010) under the assumption of existence of interfacial frictional forces described by Coulomb's law. It should be noted that the obtained expression for the normal line contact force between the wires (see Eq.…”
Section: Coupled Core-wire and Wire-wire Contactmentioning
confidence: 99%
“…An arrangement of six helical wires of radius 4.871 mm wound around a central core of radius 5.129 mm is chosen for the computation of the static behaviour. This geometry which yielded a coupled core-wire and wire-wire contact had been elaborately dealt with in the paper by Gnanavel et al [7,8] and found to exist in coupled contact mode up to a lay ratio of 7.8 and turned into core-wire radial contact afterwards. To explain the behaviour of the strand under core-wire radial contact, along with the interfacial contact effects, the same geometry adopted by Gnanavel et al [7,8] has been chosen.…”
Section: Numerical Examplementioning
confidence: 93%
“…This geometry which yielded a coupled core-wire and wire-wire contact had been elaborately dealt with in the paper by Gnanavel et al [7,8] and found to exist in coupled contact mode up to a lay ratio of 7.8 and turned into core-wire radial contact afterwards. To explain the behaviour of the strand under core-wire radial contact, along with the interfacial contact effects, the same geometry adopted by Gnanavel et al [7,8] has been chosen. Further the geometrical data of the cable has been chosen, in line with a similar research work carried out by the Costello [2] group, to explain the additional features of interfacial contact forces resulting in the axial slip and rotational slip of the helical wire on the core.…”
Section: Numerical Examplementioning
confidence: 93%
See 1 more Smart Citation